TI_GERICHTE 52.2003.343 vom 8. August 2005 , licenza edilizia in sanatoria per l'ampliamento di una casa d'abitazione - TI Tribunale d'appello (2005)
licenza edilizia in sanatoria per l'ampliamento di una casa d'abitazione